Penyalahgunaan Media Sosial Sebagai Alat Propaganda - Rety Palupi (Universitas Bina Sarana Informatika, 2019)
Changes in the communication of information continue to occur along with the advancement of technology in the digital era. Nowadays everyone can work as a journalist even though he or she has never learned the basics of journalism. The public also frequently receive information or news that raise the eyebrows — ranging from disaster threats to information about the political world. The finding of this research is that often information that circulates in the hands of Warganet is a hoax and even hate speech, despite the government efforts to reduce the spread of hoax and hate speech. With this paper, the author aims at disclosing the propaganda elements in the hoax and hate speech in the social media as in the digital era the social media is the most vulnerable in spreading of hoax news and hate speech. By utilising qualitative content analysis, the author discusses five hoax news and hate speeches which are dissected using nine propaganda practices. The conclusion obtained by the author is that the hoax news and hate speech comprise of elements of exaggeration, rhetoric, recognition and influence on a variety of parties, as well as prejudices supplemented by emotions.